HUBUNGAN PEMERIKSAAN BASIL TAHAN ASAM PADA PENDERITA TUBERKULOSIS SEBELUM DAN SESUDAH PENGOBATAN RIFAMPICIN SELAMA 6 BULAN DI RUMAH SAKIT TK III 04.06.01 WIJAYA KUSUMA PURWOKERTO - Delita Septining Tias (Yakpermas Press, 2025)
Tuberculosis is a lung infection caused by bacteria Mycobacterium tuberculosis. Early detection is one of the countermeasures to detect tuberculosis. First detection of tuberculosis namely with the Molecular Rapid Test which is one of the technologies is being developed using GeneXpert. Patients with Rapid Test results Positive molecular will be treated with rifampicin for 6 months, then further screening for Acid-Fast Bacilli is carried out microscopically to find out whether the patient is still positive for pulmonary tuberculosis or No. The aim of this research is to determine the relationship between examinations Acid-fast bacilli in tuberculosis patients with rapid molecular test results positive. This research will be carried out experimentally, namely by describing the results test the suitability of sputum examination results in tuberculosis patients with the method microscopically, then the results obtained are clear. The variables are will be observed consisting of independent variables and dependent variables. The independent variable is TCM positive, while the dependent variable is BTA examination and TB patients, then the main parameter is the level of BTA examination on TB patients while the supporting parameter is the level of positive TCM results. To determine the sample size in this study, sample size was used Hypothesis test of different proportions between 2 groups. So the minimum sample size is needed for the research is 64 people.